2020
DOI: 10.1167/tvst.9.9.43
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Corneal Nerve Fractal Dimension Analysis in Peripheral Neuropathies of Different Etiology

Abstract: The utility of corneal nerve fractal dimension analysis in peripheral neuropathies of different etiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 55 publications
1
15
0
Order By: Relevance
“…To the best of our knowledge, this is the first study to quantify function of large myelinated motor fibers in the iTAT-tg mouse model, although nerve conduction studies have been used for diagnosing peripheral neuropathy in HIV patients ( 43 46 ). Similarly, our novel finding of reduced corneal sensory nerve density is not a consequence of DOX exposure per se and is consistent with recent reports of reduced corneal nerve density in patients with HIV neuropathy ( 47 , 48 ). In a previous study we demonstrated that topical delivery of the HIV envelope protein gp120 to the eye of normal mice also leads to loss of corneal sensory nerves ( 32 ), so that two HIV-associated proteins linked with neuropathy independently impact corneal nerves.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…To the best of our knowledge, this is the first study to quantify function of large myelinated motor fibers in the iTAT-tg mouse model, although nerve conduction studies have been used for diagnosing peripheral neuropathy in HIV patients ( 43 46 ). Similarly, our novel finding of reduced corneal sensory nerve density is not a consequence of DOX exposure per se and is consistent with recent reports of reduced corneal nerve density in patients with HIV neuropathy ( 47 , 48 ). In a previous study we demonstrated that topical delivery of the HIV envelope protein gp120 to the eye of normal mice also leads to loss of corneal sensory nerves ( 32 ), so that two HIV-associated proteins linked with neuropathy independently impact corneal nerves.…”
Section: Discussionsupporting
confidence: 93%
“…Our study is limited to the use of a mouse model that expresses only one HIV-associated protein and the use of DOX to induce TAT expression. Although the iTAT-tg mouse model does not illustrate the complex interaction between HIV and HIV proteins that may impact development of HIV-DSP in humans, it does focus attention on one specific protein and its role in clinical features of HIV-DSP such as nerve conduction slowing and reduction of corneal sensory nerve density ( 2 , 47 , 48 ). Appropriate controls in our study also allowed us to segregate the impact of DOX on sensory nerve function.…”
Section: Discussionmentioning
confidence: 99%
“…CCM demonstrated no significant difference in corneal nerve fiber length, density or branch density between controls and patients with CIPN with and without small fibre neuropathy [ 216 ]. In a study comparing CCM in different peripheral neuropathies, patients with CIPN had evidence of corneal nerve fibre loss in a distinct pattern based on the corneal nerve fractal dimension, which differed from patients with diabetic neuropathy or chronic inflammatory demyelinating neuropathy [ 217 ]. A study of 70 patients with breast, colorectal, upper gastrointestinal and gynaecological cancer having received either paclitaxel ( n = 40) or oxaliplatin ( n = 30) within the past 3 to 24 months showed evidence of a significant reduction in the corneal nerve fibre and inferior whorl lengths [ 218 ].…”
Section: Corneal Confocal Microscopymentioning
confidence: 99%
“…Patients with other neurodegenerative conditions like multiple sclerosis, Wilson's disease and Friedreich's ataxia have showed a decrease in CNBD compared to controls [37][38][39]. Thus, different etiologies may impact differently on corneal nerve fibers [40].…”
Section: Discussionmentioning
confidence: 99%